2007
DOI: 10.1097/acm.0b013e318159e1ff
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Factors Associated with High Performance in Quality and Safety in Academic Medical Centers

Abstract: Distinctive leadership behaviors and organizational practices are associated with measurable differences in patient-level measures of quality and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(73 citation statements)
references
References 13 publications
3
69
1
Order By: Relevance
“…48 Qualitative studies of AMI care also provide support for many of the practices defined inTable 1. 12,49,50 In our study, a movement from the 25th to the 75th percentile in management scores was associated with a 0.17% reduction in mortality, a potentially important although modest improvement. A number of studies have indicated that process-of-care measures are correlated with lower AMI mortality, although the magnitude of effect has also been small.…”
Section: Commentmentioning
confidence: 81%
“…48 Qualitative studies of AMI care also provide support for many of the practices defined inTable 1. 12,49,50 In our study, a movement from the 25th to the 75th percentile in management scores was associated with a 0.17% reduction in mortality, a potentially important although modest improvement. A number of studies have indicated that process-of-care measures are correlated with lower AMI mortality, although the magnitude of effect has also been small.…”
Section: Commentmentioning
confidence: 81%
“…Quality must be a focus of the entire organization-not simply the responsibility of the clinical or risk-management leadership or specific change-methodology agents. 29 Integration with governance and operations is critical. A clear and discrete focus is required.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Much of it has focused on whether better management improves the efficiency and financial performance of hospitals 19,20 or on clinical engagement by hospital management. [21][22][23][24][25] We extend this literature by applying a data-driven taxonomy of managerial practices at the hospital level to provide empirical insight into the relationship among hospital governance, management, and clinical performance.…”
Section: Exhibitmentioning
confidence: 99%